2019
DOI: 10.15562/ism.v10i2.262
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan asupan serat dengan angka kejadian kanker kolorektal di RSUP Sanglah Denpasar tahun 2016 - 2017

Abstract: Background: Colorectal cancer is one of the most common cancer in Indonesia. The etiology of colorectal cancer is still unknown, but many risk factors believed may causing colorectal cancer, one of them is fiber intake of foods consumed every day like vegetables, fruits, and peanuts. There is an instrument that can be used to assess fiber intake per day. Aim: The study aimed to know how the correlation between fiber intake and colorectal cancer patient are in Sanglah General Hospital. Method: The design is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that regular consumption of fruits and vegetables is associated with a reduced incidence of chronic diseases, including cancer. 33,34 An 18-year cohort study reported that consumption of four or more servings of legumes per week had a lower incidence of colorectal adenoma than consumption of one or less servings per week. 35 These results still need attention, especially the average intake of participants is 16.7 grams / day and is below the recommended average intake of 30-40 grams / day.…”
Section: Fruit Vegetables and Legumesmentioning
confidence: 99%
“…Studies have shown that regular consumption of fruits and vegetables is associated with a reduced incidence of chronic diseases, including cancer. 33,34 An 18-year cohort study reported that consumption of four or more servings of legumes per week had a lower incidence of colorectal adenoma than consumption of one or less servings per week. 35 These results still need attention, especially the average intake of participants is 16.7 grams / day and is below the recommended average intake of 30-40 grams / day.…”
Section: Fruit Vegetables and Legumesmentioning
confidence: 99%
“…This is caused by the content of fiber, PUFA, polyphenols, and vitamins, which have a role in preventing colorectal carcinogenesis. (Swari et al, 2019) CRC develops through several genetic and epigenetic pathways. These pathways are defined on the basis of three molecular features: (i) mutations in DNA mismatch repair genes, leading to a DNA phenotype of microsatellite instability (MSI); (ii) mutations in APC and other genes that activate the Wnt pathway, marked by a chromosomal instability (CIN) phenotype, and (iii) global genome hypermethylation, resulting in the turn-off of tumor suppressor genes, which was shown to be the CpG island methylator phenotype (CIMP).…”
Section: Introductionmentioning
confidence: 99%